PENGEMBANGAN PERANGKAT PEMBELAJARAN MENULIS CERPEN BERBASIS PROYEK DAN BERPIKIR TINGKAT TINGGI PESERTA DIDIK KELAS IX SMP - Nuraini Detia Putri; Herman Budiyono; Irma Suryani (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
The learning process cannot be seperated from learning tools, namely tools that assist learning that contain lesson plans and describe in detail the skills students will acquire. The research aims to provide appropriate and effective learning tools for project-based short story writing and higher order thinking. The work employes the development research, which refers to the ADDIE model. The subjects of this study were Indonesian language teachers and students of SMPN Satu Atap 4 Tungkal Ulu. The results showed that the development of learning materials for project-based short story writing and higher-level thinking was declared valid, practical with an average score of 84.58%. The use of project-based short story writing learning tools and higher-order thinking is declared effective for improving student learning outcomes.